Mapping and cloning of pepper fruit color-related genes based on BSA-seq technology - Feng, Shuo; Zhou, Ling; Sharif, Rahat; Diao, Weiping; Liu, Jiali; Liu, Xinxin; Chen, Kunhao; Chen, Guoju; Cao, Bihao; Zhu, Zhangsheng; Liao, Yi; Lei, Jianjun; et al. (Frontiers in Plant Science, 2024)
Fruit color is an important qualitative trait that greatly influences the marketability of peppers. Fruit color can be divided into two categories. Green fruit color denotes commercial maturity, whereas ripe fruit indicates physiological maturity. Herein, segregation populations were created using the ‘D24’ with pale green in the green fruit stage, orange in the mature fruit stage, and ‘D47’ with green in the green fruit stage and red in the mature fruit stage. BSA-seq and genetic linkage map analysis revealed green fruit color was linked to (gyqtl1.1) on Chr1 and (gyqtl10.1) on Chr10, while mature fruit color was linked to Chr6. Using functional annotation, sequence, and expression analysis, we speculate that an SNP mutation in the CapGLK2 gene at the gyqtl10.1 interval could initiate premature termination of translation, thus yielding green to pale green fruits in D47. Conversely, the orange color in mature D24 fruits is due to the Indel-mediated premature termination of translation of the CapCCS gene. Our research offers a theoretical foundation for choosing different varieties of pepper fruit based on their color.